1998
DOI: 10.1038/bjc.1998.451
|View full text |Cite
|
Sign up to set email alerts
|

The suppression of fibroblast growth factor 2/fibroblast growth factor 4-dependent tumour angiogenesis and growth by the anti-growth factor activity of dextran derivative (CMDB7)

Abstract: Summary Our previous studies showed that carboxymethyl benzylamide dextran (CMDB7) blocks basic fibroblast growth factor (FGF-2)-dependent cell proliferation of a human breast epithelial line (HBL1 00), suggesting its potential role as a potent antiangiogenic substance. The derived cell line (HH9), which was transformed with the hst/FGF4 gene, has been shown to be highly proliferative in vitro and to induce angiogenic tumours in nude mice. We show here that CMDB7 inhibits the mitogenic activities of the condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…The A431 growth decrease by CMDB7 in vitro could involve the inhibition of other mitogenic growth factors. This interpretation can be strengthened by our previous studies demonstrating that CMDB7 inhibited the activity of heparin-binding PDGF and TGFb by altering their conformation, but did not change the activity of EGF and IGF1, which are not heparin-binding growth factors (Bagheri-Yarmand et al, 1997, 1998a. Independently, the possible VEGF autocrine pathway in A431 could mediate tumour cell survival by protecting them from apoptosis as it was recently reported for breast cancer MDA-MB-231 cells (Bachelder et al, 2001).…”
Section: Discussionmentioning
confidence: 65%
“…The A431 growth decrease by CMDB7 in vitro could involve the inhibition of other mitogenic growth factors. This interpretation can be strengthened by our previous studies demonstrating that CMDB7 inhibited the activity of heparin-binding PDGF and TGFb by altering their conformation, but did not change the activity of EGF and IGF1, which are not heparin-binding growth factors (Bagheri-Yarmand et al, 1997, 1998a. Independently, the possible VEGF autocrine pathway in A431 could mediate tumour cell survival by protecting them from apoptosis as it was recently reported for breast cancer MDA-MB-231 cells (Bachelder et al, 2001).…”
Section: Discussionmentioning
confidence: 65%
“…The control group received s.c. 0.1 ml of NaCl 0.9%. A tumour volume was calculated as previously described (Bagheri-Yarmand et al, 1998a).…”
Section: Xenografts In Nude Micementioning
confidence: 99%
“…Previous reports indicated that MCF-7ras cells secreted the growth factors mitogenic for BALBc/3T3 fibroblasts (Bagheri-Yarmand et al, 1998a). We investigated whether CMDB LS4 or NaPa could influence the mitogenic activity of MCF-7ras cell conditionned medium (CM) ( Figure 5).…”
Section: Effect Of Napa and Cmdb Ls4 On Mcf-7 Ras CM Mitogenic Activimentioning
confidence: 99%
See 2 more Smart Citations